Performance Analysis Of Adjacent Channel Rejection Due To Channel Reject Filter In RF Superhetrodyne Receiver Based On IEEE 802.11a Standard - Shairi, N. A; Ahmad, Badrul Hisham; Tharek, Abdul Rahman (2010)
In this paper, a performance analysis of adjacent channel rejection (ACR) due to channel select filter (CS filter) in RF superhetrodyne receiver is presented. The ACR performance analysis is based on IEEE 802.11a standard at 5.8 GHz band. This analysis is very important in order to determine the attenuation level of CS filter in early stage of filter design for RF superhetrodye receiver. This analysis has been performed in Advanced Design Software. As result, it shown that higher attenuation level is required in CS filter for low data rate (e.g. 6 Mbps) compared to high data rate (e.g. 54 Mbps). Thus, the 30 dB attenuation level at adjacent channels in the CS filter is proposed for the RF superhetrodyne receiver in order to meet ACR performance.